1993
DOI: 10.1002/ar.1092370311
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the development of the truncus arteriosus of the chick embryo heart. I. Time of appearance

Abstract: The time of appearance of the truncus arteriosus was studied in the chick embryo using an in ovo labeling technique. Three hundred embryos at stages 13-18 of Hamburger and Hamilton were selectively labeled at the distal end of the heart tube, using gelatine-india ink label; 122 of these embryos were reincubated and 111 of them reached stages 25-28. In these stages the final location of the label was determined. Only 95 of these embryos showed both a normal heart and a label located in it. The remaining embryos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In the first or “minimum” version, cardiac looping is also called “dextral‐” or “rightward‐looping” (DeHaan, 1965; Stalsberg, 1970; Olson and Srivastava, 1996). Dextral‐looping comprises only those morphogenetic events leading to the transformation of the originally straight heart tube into a c‐shaped bend/loop whose convexity is directed toward the right of the body (DeHaan, 1965; Stalsberg, 1970; Garcia‐Peláez and Arteaga, 1993; Icardo, 1996).…”
Section: Terminological Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first or “minimum” version, cardiac looping is also called “dextral‐” or “rightward‐looping” (DeHaan, 1965; Stalsberg, 1970; Olson and Srivastava, 1996). Dextral‐looping comprises only those morphogenetic events leading to the transformation of the originally straight heart tube into a c‐shaped bend/loop whose convexity is directed toward the right of the body (DeHaan, 1965; Stalsberg, 1970; Garcia‐Peláez and Arteaga, 1993; Icardo, 1996).…”
Section: Terminological Problemsmentioning
confidence: 99%
“…For example, the regional subdivisions of the c‐shaped loop are far away from their definitive topographical relationships to each other. The future ventricles lie cranial and to the right of the future atria, and a morphological subunit representing the anlage of the future great arteries (truncus arteriosus) usually has not appeared at this time point of development (Garcia‐Peláez and Arteaga, 1993).…”
Section: Terminological Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we interpret our findings and those of Ya et al (1998) and Bergwerff et al (1998) to indicate that the smooth muscle cells of the wall of the proximal region of the aortic and pulmonary arteries do not arise from the transformation of cells originating from the truncal myocardial wall. Although Burke et al (1994) also reported that the truncal myocardium transforms into smooth muscle, their conclusion was based on the expression of various ECM proteins (fibronectin, laminin, and collagen I) in the chick embryo heart at stage 18HH, a stage at which the truncus was not yet present (García Peláez and Arteaga, 1993). Interestingly, Burke et al (1994) did describe that the smooth muscle myosin and collagen VI began to be expressed in the truncus at stage 30HH.…”
Section: Discussionmentioning
confidence: 99%
“…The conus begins to appear at stage 12HH (de la Cruz et al, 1977), while the truncus starts to emerge at stages 16–17HH (García Peláez and Arteaga 1993; de la Cruz and Markwald, 1998). Since these primitive cardiac segments appear progressively and are both externally covered by a myocardial sleeve, it is hard to distinguish an external boundary between them.…”
Section: Discussionmentioning
confidence: 99%